1999
DOI: 10.1128/jvi.73.6.4786-4793.1999
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8-Encoded Thymidine Kinase and Phosphotransferase Homologues Confer Sensitivity to Ganciclovir

Abstract: Human herpesvirus 8 (HHV-8) sensitivity to the nucleoside analog ganciclovir (GCV) suggests the presence of a virally encoded kinase that catalyzes the initial phosphorylation of GCV. Analysis of the HHV-8 genome identified two candidate kinases: proteins encoded by open reading frame (ORF) 21, with homology to the herpesvirus thymidine kinases (TK), and ORF 36, with homology to the herpesvirus phosphotransferases (PT). Experiments presented here show that both ORF 21 and ORF 36 encode GCV kinase activities as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…In this regard, the ORF-36-encoded protein was the more efficient. ORF-21, but not ORF-36, also sensitised cells to killing by penciclovir, but not brivudin [71]. Ganciclovir-phosphorylating activity of the ORF-21-encoded protein has also been reported by Gustafson et al [70].…”
Section: Antiviral Therapy For Hhv-8 Infectionmentioning
confidence: 64%
See 2 more Smart Citations
“…In this regard, the ORF-36-encoded protein was the more efficient. ORF-21, but not ORF-36, also sensitised cells to killing by penciclovir, but not brivudin [71]. Ganciclovir-phosphorylating activity of the ORF-21-encoded protein has also been reported by Gustafson et al [70].…”
Section: Antiviral Therapy For Hhv-8 Infectionmentioning
confidence: 64%
“…The HHV-8 genome encodes two candidate kinases for the phosphorylation of nucleoside analogues, i.e. (i) the protein encoded by ORF-21, that has homology to the HSV and VZV thymidine kinases and (ii) the protein encoded by ORF-36 which has homology to herpesvirus phosphotransferases [70,71]. Cannon et al [71] demonstrated that both the ORF-21 and ORF-36 encoded kinases confer sensitivity to ganciclovir, as shown by ganciclovir phosphorylation and ganciclovir-mediated cell death.…”
Section: Antiviral Therapy For Hhv-8 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV, HHV-6 and KSHV encode CHPKs [16,17,19,21]. The HHV-6 and KSHV CHPKs possess both protein kinase activity and kinase activity against nucleotide analogues, as seen for HCMV UL97 [19,59]. Recombinant viruses lacking these CHPKs have not been constructed, leaving the roles of these CHPKs in viral replication unclear at present.…”
Section: Chpks Of Ebv Hhv-6 and Kshvmentioning
confidence: 99%
“…S imilarly to other double-stranded DNA (dsDNA) viruses, the vast majority of Kaposi's sarcoma-associated herpesvirus (KSHV) gene expression conforms to the eukaryotic paradigm of cap-dependent translation of a single protein per mRNA. The sole viral protein expressed exclusively from a functionally polycistronic mRNA is the ORF36 protein kinase, a viral factor that activates the c-Jun N-terminal kinase (JNK) signaling pathway and sensitizes KSHV-infected cells to ganciclovir (1)(2)(3)(4)(5)(6). The viral ORF35-37 polycistronic mRNA directs synthesis of both ORF35 and ORF36, whereas ORF37 is translated from an independent monocistronic transcript (7).…”
mentioning
confidence: 99%